Respuesta :
Answer:
x = -1
Step-by-step explanation:
3(x - 6) - 8x = -2 + 5(2x + 1)
3x - 18 - 8x = -2 + 10x + 5
-5x - 18 = 10x + 3
-15x = 15
x = -1
Answer:
[tex]x=-\cfrac{7}{5}[/tex]
Or
[tex]x=-1.4[/tex]
Step-by-step explanation:
[tex]3(x-6)-8x=-2 + 5(2x+1)[/tex]
[tex]3(x-6)-8x \:\bold{Expand}[/tex]
[tex]-2+5\left(2x+1\right)\:\bold{Expand}[/tex]
[tex]-5x-18=10x+3[/tex]
[tex]-5x-18+18=10x+3+18\:\bold{Add\:18\:to\:both\:sides}[/tex]
[tex]-5x=10x+21[/tex]
[tex]-5x-18+18=10x+3+18\:\bold{Subtract\:10x \:from\:both\:sides}[/tex]
[tex]-15x=21[/tex]
[tex]\cfrac{-15x}{-15}=\cfrac{21}{-15}\:\bold{Divide \: both\: sides\: by\: 15}[/tex]
[tex]x=-\cfrac{7}{5}[/tex]
~